Sustainable Rural Development: Strategies, Good Practices and Opportunities - Masot, Ana Nieto; Gascón, José Luis Gurría (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In 2020, a Special Issue titled "Sustainable Rural Development: Strategies, Good Practices and Opportunities" was launched, in which 16 papers were published. The aim of this monograph was to study a problem that is occurring on a global scale and, above all, in the most developed countries, which is the population emigration from rural areas to urban areas due to the labour and service opportunities offered by the latter. This is causing a demographic deterioration of rural areas, and those that remain show high rates of ageing, masculinisation, or low demographic growth. In addition, and interrelated with this demographic deterioration, there is economic and environmental degradation. Rural areas are territories with increasingly lower purchasing power, job opportunities, and services for the population, which are classified as "spaces in crisis". The papers in this Special Issue evidence the many public and private strategies that are being pursued to achieve sustainable rural development in declining areas. The diversity of approaches offer a vision of the practical application and the obstacles or difficulties that many of them are having to achieve their objectives. All of these strategies are intended to achieve economic dynamism that is respectful of the environment and from there to be able to reduce the regressive demographic processes in rural areas. These are different approaches that allow us to contribute, from scientific, holistic, and multidisciplinary knowledge, and they can help decision making in public policy and planning strategies.